2017
DOI: 10.3389/fpls.2017.01265
|View full text |Cite
|
Sign up to set email alerts
|

Silicon Supplementation Alters the Composition of Herbivore Induced Plant Volatiles and Enhances Attraction of Parasitoids to Infested Rice Plants

Abstract: Silicon (Si) is important in plant defenses that operate in a direct manner against herbivores, and work in rice (Oryza sativa) has established that this is mediated by the jasmonate signaling pathway. Plant defenses also operate indirectly, by the production of herbivore induced plant volatiles (HIPVs) that attract predators and parasitoids of herbivores. These indirect defenses too are mediated by the jasmonate pathway but no earlier work has demonstrated an effect of Si on HIPVs. In this study, we tested th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
55
0
6

Year Published

2017
2017
2023
2023

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 89 publications
(63 citation statements)
references
References 54 publications
2
55
0
6
Order By: Relevance
“…Si amendment is also reported to be involved in priming the chemical defense in plants (Ghareeb et al., ; Han et al., ; Yang, Han, Li, Li et al., ; Ye et al., ) as well as in the augmented release of herbivore‐induced plant volatiles that attract natural enemies of the attacking pests (Kvedaras, An, Choi, & Gurr, ; Liu et al., ). An important induced plant defense to sucking insects is callose deposition on sieve plates.…”
Section: Introductionmentioning
confidence: 99%
“…Si amendment is also reported to be involved in priming the chemical defense in plants (Ghareeb et al., ; Han et al., ; Yang, Han, Li, Li et al., ; Ye et al., ) as well as in the augmented release of herbivore‐induced plant volatiles that attract natural enemies of the attacking pests (Kvedaras, An, Choi, & Gurr, ; Liu et al., ). An important induced plant defense to sucking insects is callose deposition on sieve plates.…”
Section: Introductionmentioning
confidence: 99%
“…JA and SA regulate defenses against herbivores, particularly JA controls cell-content-feeding and tissue-chewing insects 16,17 while SA and JA together regulate the defense against phloem-feeding insects 18 . It has been shown recently that Si induces JA-mediated defense responses against insects and pests 19 , indicating that Si can enhance the plant resistance against herbivores by regulating the defense responsive phytohormone pathways. Si also induces the priming process in host plant by sensitizing and preparing the plant for quick responses against the future herbivore attacks [20][21][22] .…”
mentioning
confidence: 99%
“…Organization of conserved motifs identified in finger millet silicon transporter proteins was predicted by MEME tools. The sequence and motifs identified were indicated by different coloured(1)(2)(3)(4)(5)(6)(7)(8)(9)(10)(11)(12)(13)(14)(15)(16)(17)(18)(19)(20). (2020) 10:4229 | https://doi.org/10.1038/s41598-020-61182-0…”
mentioning
confidence: 99%
“…Although silicon and nitric oxide positively affect the growth and development of some crops, this effect was not observed in the current analysis. This result may be related to the influence of these chemicals on plant resistance because increased resistance could cause photoassimilates to be directed toward defense mechanisms instead of vegetative growth . In fact, the current analysis showed a significant interaction between inducers and attack by M. spectabilis nymphs and adults with regard to phenolic compound concentrations in forage grass species.…”
Section: Discussionmentioning
confidence: 66%
“…The current study also demonstrated that plants attacked by adult insects showed a greater concentration of phenolic compounds than control plants or plants attacked only by nymphs and also proved to have greater concentrations of foliar silicon. Several authors have demonstrated that insect infestation triggers the production of secondary compounds and antiherbivore enzymes, and affects the emission of volatile compounds . According to Lattanzio et al , resistance traits in plants require the replacement of resources.…”
Section: Discussionmentioning
confidence: 99%